O fenomenie dostosowania na gruncie praktyki edukacji inkluzyjnej - Gajdzica, Zenon (Kultura-Społeczeństwo-Edukacja, 2016)
Adaptation is a notion frequently used in legal acts which normalize the educational situation of learners with disabilities. This has made adaptive activity an immanent part of school practice. The thesis is put forward that adaptation is an ambiguous category and therefore is used in various ways or is frequently overused. In many circumstances, this notion has become a skeleton key which opens the space for free lowering of educational requirements and schematic simplification of educational situations, which frequently hinders learners’ development. The study is aimed at explaining the phenomenon of adaptation and at considering its possible variants with special regard for the context of inclusive education of disabled learners.